MENINGKATKAN KINERJA KARYAWAN: PERAN DISIPLIN KERJA, KOMPETENSI, DAN LINGKUNGAN KERJA DI SEKRETARIAT DPRD KABUPATEN MALANG - Oktavia Diaz, Tedi; Endayani, Fatmasari; Dian Puspasari, Ernita; Cahyantini, Aryntika; Saman, Saman (Jurnal Daya Saing, 2024)
This study aims to analyze the influence of work discipline, competence, and work environment on employee performance at the Secretariat of DPRD Kabupaten Malang. Using a quantitative approach, data were collected through a survey of 75 randomly selected employees from a total population of 95 employees. Data analysis was conducted using multiple linear regression to determine the contribution of each variable to employee performance. The results showed that competence did not have a significant effect, while work discipline and the work environment had a significant positive impact on employee performance. The work environment was found to be the most dominant factor influencing performance, followed by work discipline. These findings highlight the importance of improving work discipline, developing competence, and creating a conducive work environment to enhance employee performance in government organizations. The practical implications of this study suggest that management should focus on policies and programs that strengthen discipline, enhance competence, and improve the work environment to achieve optimalperformance.